VALIDATION OF THE E-LEARNING PRACTICES INSTRUMENT - Nor Hasnida Che Md Ghazali; Hishamuddin Ahmad; Syaza Hazwani Zaini; Zahari Suppian; Siti Fazlyana Mat Husin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The success of the Malaysian Education Blueprint 2015-2025 could be achieved by the effective practices of e-learning. E-learning is not just an option today but has become a necessity when the pandemic covid-19 strikes the world. Therefore, this study aims to validate an instrument of an e-learning practice among student teachers in a public university. 139 respondents are randomly selected from undergraduate students from one of the public universities in Malaysia. In order to measure the suitability of each item and validate the instrument, exploratory factor analysis (EFA) is used. The findings of the study show that all load factor values exceed 0.5 so all items are accepted for real study. This instrument has a high degree of validity and reliability to determine the e-learning practices among university students.